2003
DOI: 10.1002/sia.1636
|View full text |Cite
|
Sign up to set email alerts
|

Are measured values of the Auger parameter always independent of charging effects?

Abstract: In x-ray photoelectron spectroscopy (XPS) the Auger parameter is often used to study the electronic properties of elements, particularly in insulator materials, because this parameter is assumed to be independent of charging effects. In this paper we report on subtle differences in sample structure and experimental conditions for which the sample potential may not remain constant during the measurements for some spectrometers or experimental arrangements; for such conditions the Auger parameter is not independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…11,12,18 However, special care must be given to measurement conditions when investigations of nonconducting material on insulating bulk substrates are carried out. 29 For SnO 2 deposited on Al 2 O 3 we used the thin film substrate (cf. Experimental), whereas on Sb 2 O 3 single crystals charging artifacts in R′ were avoided by leaving the sample floating without a connection to earth during the measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12,18 However, special care must be given to measurement conditions when investigations of nonconducting material on insulating bulk substrates are carried out. 29 For SnO 2 deposited on Al 2 O 3 we used the thin film substrate (cf. Experimental), whereas on Sb 2 O 3 single crystals charging artifacts in R′ were avoided by leaving the sample floating without a connection to earth during the measurement.…”
Section: Resultsmentioning
confidence: 99%
“…16,28 BE referencing of the spectra taken with the Al 2 O 3 substrate was done with respect to the Al 2p peak at 75 eV. With these reference values, the Sn photoemission parameters (i.e., Sn 3d 5/2 and R′) of a thick film of SnO or SnO 2 compare well with the BE and R′ values taken for thick SnO 2 and SnO layers on sputter-cleaned copper 29 or silver. 9 In a previous paper, 29 we found that for insulator plates as substrates, charging effects may influence the value of the Auger parameter.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…When these lines split in two peaks, there are two Auger parameters for the same sample. Since each spectrum suffers shifts in the same amount, the Auger parameter should not depend on the charging effects or the procedure used to fix the energy scale, although some subtle dependence on charging effects has been reported [48]. The Auger parameter is shown in Table 1.…”
Section: Auger Parametermentioning
confidence: 98%
“…[37][38][39][40] However, a is also prone to higher measurement errors compared to the photoelectron BE position. As suggested in the literatures, 29,41 errors in a were minimized by stabilizing the surface potential using a constant low energy flood gun potential difference and current for different experiments and recording the measurement after sufficiently long periods of x-ray exposure (10 min) to reach equilibrium.…”
Section: In-situ Xps Surface Analysismentioning
confidence: 99%